The chickpea root rot complex in Saskatchewan, Canada- detection of emerging pathogens and their relative pathogenicity - Armstrong-Cho, Cheryl; Sivachandra Kumar, Nimllash Thangam; Kaur, Ramanpreet; Banniza, Sabine (Frontiers in Plant Science, 2023)
Chickpea fields in Saskatchewan, one of the three Canadian prairie provinces, have suffered from major health issues since 2019, but no definitive cause has been determined. Field surveys were conducted in Saskatchewan in 2020 and 2021 in order to develop a better understanding of root rot pathogens associated with chickpea. Root samples were analyzed for the presence of 11 potential chickpea root rot pathogens using end-point PCR. Fusarium redolens, F. solani and F. avenaceum were the most prevalent pathogen species detected in both survey years. The cause of Fusarium wilt in chickpea, F. oxysporum f. sp. ciceris, was not detected in either year, nor were Phytophthora spp. and Verticillium albo-atrum. Berkeleyomyces sp. was detected in one field in each year, and Verticillium dahliae was detected in several fields sampled in 2021. These two pathogens have not been reported previously on chickpea in Saskatchewan. The prevalence of Fusarium species obtained from 2021 root isolations was similar to that determined by molecular tests, with frequent isolation of F. redolens, F. oxysporum, F. avenaceum and F. solani. A series of indoor pathogenicity testing compared root disease severity caused by a selection of 16 isolates of six Fusarium species and single isolates of V. dahliae, Berkeleyomyces sp. and Macrophomina phaseolina. Results showed that select isolates of F. avenaceum were the most aggressive of the Fusarium isolates on chickpea. Despite relatively low inoculum density, a highly aggressive isolate of F. avenaceum caused severe stunting and more root rot symptoms than single isolates of V. dahliae, Berkeleyomyces sp. and M. phaseolina under the test conditions.